2006
DOI: 10.1111/j.1478-3231.2006.01282.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of staging systems to predict survival in hepatocellular carcinoma

Abstract: Child-Pugh score and alpha-fetoprotein levels were the only independent predictors of survival in patients with HCC. Child-Pugh score showed a better prediction value for survival when compared with MELD. BCLC is more accurate than the other prognostic models evaluated in this investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 38 publications
2
17
1
Order By: Relevance
“…This includes early identification due to screening, or to diagnosis later in the disease progression consequent on complications from tumor growth, or from hepatic failure. Many scoring and classification systems have taken the twin issues of cirrhosis and tumor extent into account, including those of Okuda, CLIP, BCLC, CUPI, SLiDE, JIS, and Tokyo scores, amongst others [3][4][5][6][7][8][9][10][11] and several papers have recently compared multiple staging systems [12][13][14][15][16][17][18][19][20][21][22][23]. They have been mainly intended to aid in patient selection for surgery, loco-regional therapy such as RFA or TACE, or palliative care.…”
Section: Introductionmentioning
confidence: 99%
“…This includes early identification due to screening, or to diagnosis later in the disease progression consequent on complications from tumor growth, or from hepatic failure. Many scoring and classification systems have taken the twin issues of cirrhosis and tumor extent into account, including those of Okuda, CLIP, BCLC, CUPI, SLiDE, JIS, and Tokyo scores, amongst others [3][4][5][6][7][8][9][10][11] and several papers have recently compared multiple staging systems [12][13][14][15][16][17][18][19][20][21][22][23]. They have been mainly intended to aid in patient selection for surgery, loco-regional therapy such as RFA or TACE, or palliative care.…”
Section: Introductionmentioning
confidence: 99%
“…26 In our study, we employed a MELD score Ͻ10 or Ն10 as a cut-off, consistent with previous reports. 27 A MELD Ͻ10 identifies patients that should not be listed for transplantation, because the surgical risk exceeds that corresponding to the natural history of the disease. 28 Also, patients with a MELD between 10 and 19 have been reported to have a 6.0% mortality at 3 months, compared with a 1.9% mortality of those with a MELD Ͻ9.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have clearly indicated that Okuda's score has lower prognostic performance than more recent classifications [6,7,12] and that its use is no longer justified. On the other hand, several studies have found a better performance of the BCLC staging system when compared to other recent classifications [3,12,13]. In the study by Marrero et al [12] performed in 239 patients with cirrhosis and HCC, BCLC classification had the best predictive power for survival when compared to six other prognostic models (Okuda, TNM, CLIP, GRETCH, CUPI, and JIS classifications).…”
Section: See Article Pages 108-117mentioning
confidence: 95%
“…Accordingly, survival is strongly influenced by factors related both to tumour extension and liver impairment as well as the occurrence of new tumours. The classifications, including variables only related either to tumour burden or liver function, such as Tumour Node Metastasis (TNM) and Child-Pugh classifications, have obviously insufficient performance in patients with HCC [2,3]. From the first popular classification proposed by Okuda et al [4] in 1985 to more recent models such as BCLC (Barcelona Clinic Liver Cancer) [5], GRETCH (Groupe d'Etude et de Traitement du Carcinome Hépatocellulaire) [6], CLIP (Cancer of Liver Italian Program) [7], CUPI (Chinese University Prognostic Index) [8], and JIS (Japanese Integrated System) [9], all classifications combine parameters reflecting tumour extension (number and size of nodules, vascular invasion, and serum alpha-fetoprotein level) and liver impairment (serum bilirubin, serum albumin, prothrombin activity, ascites, and degree of portal hypertension).…”
Section: See Article Pages 108-117mentioning
confidence: 99%